Animation Video Based on Tri Kaya Parisudha in the Topic of Cultural Diversity - I Gusti Ngurah Agung Darma Putra; I Wayan Sujana (Universitas Pendidikan Ganesha, 2021)
Lack of innovative learning media and the application of conventional methods that have an impact on students' interest and understanding of the content of social studies lessons. The purpose of this study was to develop an animated video based on local wisdom, Tri Kaya Parisudha, in social studies learning in the fourth grade of elementary school. This research is a development research using the ADDIE model. The subjects of this study were one lecturer as an expert on subject content, one lecturer as an expert in learning design, one lecturer as an expert in learning media, and twelve fourth grade elementary school students for individual trials and small group trials. The data collection method used in this study is a non-test method using a questionnaire with the instrument used in the form of a questionnaire/questionnaire. The data analysis technique used is descriptive quantitative analysis technique. Based on the results of data analysis, the results of the validity test results by subject matter content experts obtained a score of 95.83% (very good); the results of the validity test by instructional design experts obtained a score of 85% (good); the results of the validity test by learning media experts obtained a score of 88.33% (good); individual trial results obtained a score of 95.83% (very good); and the results of the small group trial obtained a score of 97.50% (very good). Thus, it can be concluded that Tri Kaya Parisudha's video animation based on local wisdom is appropriate to be used as a learning medium for social studies subject matter for grade IV elementary school. The implication of this research is that the learning media of Video Animation based on Local Wisdom Tri Kaya Parisudha can make students learn independently, so that the learning process becomes more interesting, effective, and has a positive effect on student learning outcomes.